Gender [im]balance in productive and reproductive labor among livestock producers in Colombia: Implications for climate change responses - Arora, Diksha; Arango, Jacobo; Burkart, Stefan; Chirinda, Ngonidzashe; Twyman, Jennifer (2017)
Roles and responsibilities in livestock production and household maintenance are segregated along gender lines. Men’s and women’s participation in the livestock sector varies by tasks. Women combine livestock production, particularly, milk processing activities with the responsibility of household and care work.  Men’s and women’s indirect contribution with regard to maintenance of the household and care provision to family members is also crucial for healthy and smooth functioning of livestock productive activities and therefore, must be accounted for in policy decisions, including those related to changing climate.  As a response to climate change induced drought, men, and particularly women, are investing their labor in alternative sources of income to pay for water provision services to meet the water demands of their animals. For women who already face the double burden of productive and reproductive work, this coping mechanism may deepen their time poverty.